Posttraumatic Stress Disorder Is Associated With Endothelial Dysfunction in Women With HIV - Nishant Vatsa, MD; Alireza Rahbar, MD; Tanveer Kauser, MPH; Ariel Kirksey, BS; Daniel A. Gold, MD; Vardhmaan Jain, MD; Matthew E. Gold, MD; Heqiong Wang, MD, MPH; Christina Mehta, PhD, MSPH; Caitlin A. Moran, MD; Alicia K. Smith, PhD; Kimbi Hagen, EdD, Med; et al. (JACC: Advances)
Background: HIV induced endothelial dysfunction (ED) contributes to cardiovascular disease (CVD) in women with HIV (WWH). Although psychosocial stress has been implicated in the development of CVD in HIV, its impact on ED in WWH remains unknown. Objectives: The authors hypothesized that posttraumatic stress disorder (PTSD) and HIV interact to contribute to ED in WWH. Methods: We enrolled 87 women from the Women’s Interagency HIV Study in Atlanta, Georgia, who reported previous trauma and completed the PTSD Checklist: Civilian Version (PCL-C), which assesses PTSD symptom severity (PCL-C score) and PTSD status (PCL-C >44). Brachial artery flow-mediated dilation (FMD) was measured to assess endothelial function. The impact of PTSD, HIV, and their interaction on endothelial function was evaluated using linear regression models adjusted for demographics, CVD risk factors, depressive symptoms, and statin use. Results: Overall, 55 (63.2%) had HIV, 24 (27.5%) had PTSD, and 13 (14.9%) had both. Those with PTSD were more likely to smoke (18 [75%] vs 28 [44.4%], P = 0.02) and have depressive symptoms (14 [58.3%] vs 18 [28.6%], P = 0.02) than those without PTSD. In adjusted models, the HIV-PTSD (severity and status) interaction effect on FMD was significant (P = 0.01). Both PTSD severity (β per 10-point increase: −0.72% [95% CI: −1.22 to −0.21], P = 0.01) and PTSD status (β: −2.51% [95% CI: −4.21 to −0.77], P = 0.01) were independently associated with lower FMD in WWH but not in those without HIV. Conclusions: PTSD is independently associated with ED in WWH. Whether treatment for PTSD improves ED and CVD in WWH needs further study.